The degree of knowledge about the use of hormonal contraceptive agents in a communitarian pharmacy in Zaragoza (Spain) - Petruta Dimitriu, Ana; García-Jiménez, Emilio; Martínez Martínez, Fernando; Moreno López, Ana (Ars Pharmaceutica (Internet), 2009)
Introduction: It is important to know very well each day how one can use a hormonal contraceptive agent due to the introducing of some new contraceptive methods and new pharmaceutical forms of administration, and how one can react when it comes to the appearance of some secondary effects.Objective: To assess the degree of knowledge among the female users of hormonal contraceptive agents who attended a communitarian pharmacy in Zaragoza, Spain. Methods: Observational, descriptive, cross-sectional study by means of an administered questionnaire to 148 users who attended a communitarian pharmacy in Zaragoza. Results: 48.6% of the women who responded to the questionnaire have an average degree of knowledge as opposed with single 23% of them who have a degree of a high knowledge.In addition, the users who know more about their method are those who are taking the birth control (83.33% of them) in comparison with the users who take the vaginal ring or the transdermal patch (10.13% and 3.33%, respectively) [CI-95%, X2=34,898, p=0.000]. No statistical significance was found between the degree of knowledge and other variables that influence in the profile of the user (age, nationality, studies, smoke habit, concomitant diseases and type of prescription). Conclusions: Single one of three users knows about the usage of a hormonal contraceptive agent and the degree of knowledge it is not influenced by the user’s profile. It is important to design campaigns of sanitary education about the correct usage and the knowledge of the new contraceptive methods that have been appearing over the last few years.